A modal space based direct method for vortex-induced vibration prediction of flexible risers. (15th March 2018) - Lu, Ziqi; Fu, Shixiao; Zhang, Mengmeng; Ren, Haojie; Song, Leijian
Abstract: A modal space based direct method is developed for vortex-induced vibration (VIV) prediction of flexible risers. A VIV response solution model is established in modal space, consisting of a hydrodynamic force equation and a dynamic response equation. Adopting a non-iterative root-search method in modal space, the equation set gets solved directly without power-balance iterations. This direct method is compared against conventional empirical models, with its validity and applicability verified. This method entirely gets rid of convergence problems during predictions, which is conducive to practical engineering applications and puts forward fresh ideas for further development of empirical models for VIV prediction. Highlights: The modal space based direct method avoids power-balance iterations during response calculations. A solving model for VIV responses is established in modal space and gets solved by a non-iterative root-search method. This method is compared against conventional empirical models through prediction cases, with its validity verified.